Hypoxia-induced soluble CD137 in malignant cells blocks CD137L-costimulation as an immune escape mechanism. (2nd January 2016) - Labiano, Sara; Palazón, Asis; Bolaños, Elixabet; Azpilikueta, Arantza; Sánchez-Paulete, Alfonso R.; Morales-Kastresana, Aizea; Quetglas, Jose I.; Perez-Gracia, José L.; Gúrpide, Alfonso; Rodriguez-Ruiz, Maria; Aznar, M. Angela; Jure-Kunkel, Maria; et al.
ABSTRACT: Hypoxia is a common feature in solid tumors that has been implicated in immune evasion. Previous studies from our group have shown that hypoxia upregulates the co-stimulatory receptor CD137 on activated T lymphocytes and on vascular endothelial cells. In this study, we show that exposure of mouse and human tumor cell lines to hypoxic conditions (1% O2 ) promotes CD137 transcription. However, the resulting mRNA is predominantly an alternatively spliced form that encodes for a soluble variant, lacking the transmembrane domain. Accordingly, soluble CD137 (sCD137) is detectable by ELISA in the supernatant of hypoxia-exposed cell lines and in the serum of tumor-bearing mice. sCD137, as secreted by tumor cells, is able to bind to CD137-Ligand (CD137L). Our studies on primed T lymphocytes in co-culture with stable transfectants for CD137L demonstrate that tumor-secreted sCD137 prevents co-stimulation of T lymphocytes. Such an effect results from preventing the interaction of CD137L with the transmembrane forms of CD137 expressed on T lymphocytes undergoing activation. Indeed, silencing CD137 with shRNA renders more immunogenic tumor-cell variants upon inoculation to immunocompetent mice but which readily grafted on immunodeficient or CD8 + T-cell-depleted mice. These mechanisms are interpreted as a molecular strategy deployed by tumors to repress lymphocyte co-stimulation via CD137/CD137L.